Synthesis and EPR-spectroscopic characterization of the perchlorotriarylmethyl tricarboxylic acid radical (PTMTC) and its 13C labelled analogue (13C-PTMTC). Issue 9 (17th February 2017) - Elewa, Marwa; Maltar-Strmečki, Nadica; Said, Mohamed M.; El Shihawy, Hosam A.; El-Sadek, Mohamed; Frank, Juliane; Drescher, Simon; Drescher, Malte; Mäder, Karsten; Hinderberger, Dariush; Imming, Peter
Abstract : PTMTC with 50% 13 C labelling allows for oxygen determination ( 12 C-PTMTC ) and insights into the local, nanoscopic environment ( 13 C-PTMTC ). Abstract : A hydrophilic tris(tetrachlorotriaryl)methyl (tetrachloro-TAM) radical labelled 50% with 13 C at the central carbon atom was prepared. The mixture of isotopologue radicals was characterised by continuous wave and pulsed X-band electron paramagnetic spectroscopy (EPS). For the pharmaceutical and medical applications planned, the quantitative influence of oxygen, viscosity, temperature and pH on EPR line widths was studied in aqueous buffer, DMSO, water–methanol and water–glycerol mixtures. Under in vivo conditions, pH can be disregarded. There is a clear oxygen dependence of the width of the 12 C isotopologue single EPR line in aqueous solutions while changes in rotational motion (viscosity) are observable only in the doublet lines of the central carbon of the 13 C isotopologue. The tetrachloro-TAM proved to be very stable as a solid. Its thermal decay was determined quantitatively by thermal annealing. Towards ascorbic acid as a reducing agent and towards an oocyte cell extract it had a half-life of approx. 60 and 10 min. Thus for in vivo applications, 50% 13 C tetrachloro-TAMs are suitable for selective and simultaneous oxygen and macroviscosity measurements in a formulation, e.g. nanocapsules.